Influences of annealing temperature on characteristics of composite materials consisting of multi-walled carbon nanotubes and Pb(Zr0.52Ti0.48)O3 thin films - Kwak, Jin Ho; Han, Jin Kyu; Cho, Sam Yeon; Bu, Sang Don (Journal of the Korean Physical Society, 2012)
We report the synthesis and the characterization of composite materials consisting of multi-walled carbon nanotubes and Pb(Zr 0.52 Ti 0.48 )O 3 (CNT-PZT) in a film structure. The CNT-PZT films were prepared by using a sol-gel process, a spin-coating method and a rapid thermal annealing process. CNT bundles in 2-methoxyethanol solution were mixed with a 7-wt% PZT sol-gel solution. The CNT-PZT solution was deposited onto (111) Pt/Ti/SiO 2 /Si substrates by spin-coating at 3000 rpm for 60 s and was then pyrolyzed. The samples were annealed at various temperatures in an oxygen atmosphere for crystallization. The morphological, structural and electrical properties of CNT-PZT composite films were studied with a field-emission scanning electron microscope, X-ray diffraction and polarization-voltage hysteresis loops, respectively. We found that, during the annealing process, the thickness of CNT-PZT films dramatically decrease, especially in the range of 500 to 600 °C, which may be related with the loss of CNTs in that temperature region due to burning. The CNTs also affect the orientation of and the number of defects in the PZT films, which change the ferroelectric properties of the films.